ANALISIS UNSUR BATIN DALAM PUISI “KONTEMPLASI” KARYA IKA MUSTIKA - Setiawan, Sandi (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Literary works are not only meant as works that have beauty in each string of words, but every literary work contains meaning or meaning that can be felt by living it. Poetry is one form of fiction that implies meaning. Poetry can be a motivation for lovers of writing, especially for readers who want to know the meaning or meaning contained in a poem. The author is interested in analyzing the inner elements of poetry contained in a poem by Ika Mustika entitled "Contemplation", the purpose of this study is to find out the inner elements contained in the work. The method used in this study is a qualitative descriptive method that presents the results of research using words, and the results of this study indicate that the work of poetry entitled "Contemplation" contains meaning and is full of meaning when viewed from its inner structure.